Sikap Guru Dalam Menghadapi Siswa Yang Menggunakan Diksi Yang Terinspirasi TikTok di SDIT Persis Tarogong Garut - 10080021246, Marsyanda Rizki Amalia; Raditya Pratama Putra (Bandung Conference Series: Communication Management, 2025)
Abstract. The use of social media, particularly TikTok, has become a significant phenomenon in the lives of children and teenagers, including within educational settings. Trends in content and language that develop on TikTok influence word choice in everyday communication, which has the potential to alter communication norms in schools. This phenomenon challenges teachers in guiding students to continue using language that aligns with Islamic values and school norms. SDIT Persis Tarogong Garut, as a school based on religious values, also experiences this phenomenon, where students tend to use informal language popularized by TikTok. This study aims to analyze teachers' attitudes in addressing the diction choices of TikTok-using students, including their understanding, feelings, and actions toward changes in students' word choices in the school environment. The novelty of this research lies in its specific focus on a particular social media platform—TikTok—in influencing children’s diction, as well as the application of Islamic values in evaluating teachers’ attitudes. The research method employed is quantitative with a descriptive approach. Data were collected through questionnaires distributed to teachers at SDIT Persis Tarogong Garut. The results show that although some teachers are concerned about the negative effects of using diction that does not align with school norms, the majority tend to have an adaptive attitude and strive to understand the social and cultural context influencing the students. Abstrak. Penggunaan media sosial khususnya TikTok telah menjadi fenomena yang signifikan dalam kehidupan anak – anak dan remaja termasuk di lingkungan pendidikan. Tren konten dan bahasa yang berkembang di TikTok berdampak pada pilihan diksi dalam komunikasi sehari – hari, yang dapat berpotensi merubah norma komunikasi di sekolah. Fenomena ini menantang guru dalam membimbing siswa untuk tetap menggunakan bahasa yang sesuai dengan nilai – nilai keislaman dan norma sekolah. SDIT Persis Tarogong Garut sebagai sekolah berbasis nilai – nilai agama juga mengalami fenomena ini, di mana siswa cenderung menggunakan bahasa informal yang populer dari TikTok. Penelitian ini bertujuan untuk menganalisis sikap guru dalam menghadapi pemilihan diksi siswa pengguna TikTok yang mencakup pemahaman, perasaan, dan tindakan guru terhadap perubahan diksi siswa di lingkungan sekolah. Kebaruan penelitian ini terletak pada fokusnya yang spesifik terhadap suatu platform media sosial yaitu TikTok dalam mengubah diksi anak – anak serta penerapan nilai – nilai keislaman dalam mengevaluasi sikap guru. Metode penelitian yang digunakan adalah kuantitatif dengan pendekatan deskriptif. Data dikumpulkan melalui kuesioner yang disebarkan kepada guru – guru di SDIT Persis Tarogong Garut. Hasil penelitian menunjukkan bahwa meskipun beberapa guru mengkhawatirkan dampak negatif dari penggunaan diksi yang tidak sesuai dengan norma sekolah, mayoritas guru cenderung memiliki sikap yang adaptif dan berusaha memahami konteks sosial budaya yang memengaruhi siswa.